Konstruksi Ideal Badan Regulasi Nasional Dalam Bingkai Hukum Positif Indonesia (RechtJiva, 2024)
Mandate of Law Number 15 of 2019 concerning Amendments to Law Number 12 of 2011 concerning the Establishment of Laws and Regulations which mandates the establishment of ministries or institutions that carry out government affairs in the field of forming laws and regulations. However, until December 2023, the ministry or institution that the author further proposes the nomenclature of the National Regulatory Agency has not yet been formed and has implications for the legal certainty aspect of the establishment of the institution. In addition, the a quo law also does not provide a complete regulatory concept for the institutional format to be regulated in the Presidential Regulation. Based on this, this study raises the formulation of the problem (1) how is the legal politics of the establishment of the National Regulatory Agency in Indonesia? and (2) what is the regulatory concept for the establishment of the National Regulatory Agency in the Indonesian legal system? Then, this research uses normative juridical methods using statutory approaches and conceptual approaches. Legal materials used include primary, secondary and tertiary legal materials with legal material tracing techniques, namely literature studies and internet media. Therefore, there is a need for the concept of institutional arrangements which in this case the author formulates into 4 (four) main things. First, the regulation of the National Regulatory Agency through a Presidential Regulation. Second, the organizational structure of the National Regulatory Agency. Third, the National Regulatory Agency. Fourth, the accountability pattern of the National Regulatory Agency.